High-elasticity breathable cream mask cloth and preparation method thereof
By modifying cotton fibers and tense fibers and using modifiers and nanomaterials to form a highly elastic and breathable cream mask film cloth, the existing film cloth has solved the shortcomings in breathability, hygroscopy, antibacteriality and elasticity, and achieved higher liquid absorption and antibacterial properties, meeting the high demand of users.
Patent Information
- Application Number
- CN202411952281.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The existing cream mask masks have shortcomings in breathability, moisture absorption, antibacteriality and elasticity, which are difficult to meet the high demand of users.
By modifying cotton fibers and tense fibers, and using a specific proportion of modifiers and nanomaterials, a highly elastic and breathable cream mask film cloth is formed. The membrane cloth improves its liquid absorption, antibacteriality and breathability through hydrotubing and PUR glue compounding technology.
It realizes the high elasticity and good breathability of the cream mask mask cloth, improves the liquid absorption and antibacterial properties, and meets the users' needs for long-term moisturizing effect and product safety.
Smart Images

Figure BDA0005215132780000111 
Figure BDA0005215132780000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cosmetics, and in particular relates to a highly elastic and breathable cream mask cloth and a preparation method thereof. Background Art
[0002] Traditional facial masks are soaked with flowing essence liquid on both sides, are not waterproof, cannot penetrate in one direction, and are difficult to apply to cream-like products. Cream mask cloth is a special form of mask that combines the characteristics of cream and mask. Usually, this mask can absorb and lock the cream-like essence well. When used, the mask cloth fits closely to the skin, helping the skin to better absorb the active ingredients.
[0003] Cream mask fabrics do face many technical challenges in the design and production process, especially in terms of breathability, moisture absorption rate, antibacterial properties and elasticity. These properties are crucial to improving the user experience and product effectiveness: (1) Breathability: When the mask is fitted to the skin, if the breathability is poor, the carbon dioxide on the skin surface may not be effectively discharged, which in turn affects skin health. 2. Moisture absorption rate: The fabric needs to have good moisture absorption capacity so that it can effectively absorb and retain the essence in the cream, but if the moisture absorption rate is too high, it may also cause the essence to be lost too quickly. 3. Antibacterial property: During the production and storage process of the mask, if it does not have good antibacterial properties, it is easy to breed bacteria and affect product safety. 4. Elasticity: The mask fabric needs to have a certain degree of elasticity to adapt to different face shapes and ensure a close fit, but excessive elasticity may cause the mask to deform and affect the user experience.
[0004] The existing technology mainly adjusts the proportion and structure of the mask cloth material to find a suitable elastic range, which can ensure the fit of the mask without causing deformation of the mask due to excessive stretching. In order to ensure the elasticity of the mask cloth, the cream mask cloth on the market usually uses a conventional elastic film, PU film, but the air permeability and moisture absorption rate of PU film are poor, and the effect of applying it to the cream mask cloth is not ideal and cannot meet the needs of consumers.
[0005] Therefore, there is an urgent need for a highly elastic and breathable cream mask cloth and a preparation method thereof. Summary of the invention
[0006] The purpose of the invention is to provide a highly elastic and breathable cream mask cloth and a preparation method thereof.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] A method for preparing a highly elastic and breathable cream mask cloth, the method comprising the following steps:
[0009] (1) opening the cotton fibers by a loosening machine, and then feeding them into a cotton box of a carding machine for carding to obtain a cotton fiber web; placing the cotton fiber web in a closed cotton bunker, spraying a modifier into the cotton bunker, wherein the modifier comprises the following raw materials in parts by weight: 12-15 parts of modified chitosan, 15-18 parts of polyethylene glycol, 4-7 parts of a surfactant, and 110-120 parts of water; setting the cotton bunker temperature to 45-50° C. for simmering treatment for 7-9 hours, subjecting the cotton bunker to a natural cooling treatment, during which a steam valve in the cotton bunker is opened to spray steam humidification until the humidity is 15-17%; closing the steam valve, setting the cotton bunker temperature to 47-52° C. for simmering treatment for 30-35 hours, and after cooling to room temperature, opening the cotton bunker to obtain the modified cotton fiber web;
[0010] The Tencel fibers are opened by an opener, and then fed into a cotton box of a carding machine for carding to obtain a Tencel fiber web, and the Tencel fiber web is modified to obtain a modified Tencel fiber web;
[0011] (2) The modified cotton fiber web and the modified Tencel fiber web are laid flat, and then subjected to hydroentanglement treatment to obtain a modified cotton fiber layer and a modified Tencel fiber layer, respectively. The modified cotton fiber layer and the modified Tencel fiber layer are compounded with PUR glue; the glue weight of the PUR glue is 3-4 g / m 2 The glue application area accounts for 10%-20% of the mask cloth, and the glue application area is circular and evenly distributed; the glue application method is the gravure gluing process, the depth of the gravure roller's gluing concave points is 0.2-0.8mm, and the material is ceramic ceramic; a highly elastic and breathable cream mask cloth is obtained.
[0012] Furthermore, the amount of the modifier added is 40-45% of the mass of the cotton fiber web.
[0013] Furthermore, the preparation method of the modified chitosan comprises the following steps: adding 5 parts by weight of chitosan to 160-180 parts by weight of an acetic acid aqueous solution with a volume concentration of 2-4%, and after dissolving, continuing to add 120-140 parts by weight of ethanol, adjusting the pH value to 5-6 with 0.1-0.2 mol / L sodium hydroxide aqueous solution, adding 0.4-0.8 parts by weight of octadecyl aldehyde and 0.004-0.006 parts by weight of sodium cyanoborohydride, stirring at 25-30° C. for 25-30 hours, adjusting the pH value to 7 with 0.1-0.2 mol / L sodium hydroxide aqueous solution, adding 220-240 parts by weight of ethanol for precipitation, centrifuging, washing, and freeze-drying to obtain the modified chitosan.
[0014] Chitosan was purchased from Qingdao Bozhi Huili Biotechnology Co., Ltd., water-soluble chitosan, deacetylation degree ≥ 90%. Octadecyl aldehyde: CAS: 638-66-4.
[0015] The liquid absorption of the cream mask cloth on the market is generally low, and the lower cloth cannot absorb enough cream essence, causing the skin to be unable to obtain enough moisture and moisturizing ingredients. The present invention can improve the liquid absorption of the mask cloth by modifying cotton fiber, and can absorb more cream essence, which means that more moisturizing ingredients can be absorbed by the skin, thereby providing a longer moisturizing effect. The present invention improves the hydrophilicity of the cotton fiber net by modifying chitosan, and simultaneously finds in the experiment that the use of octadecyl aldehyde modification effect is better than octadecyl benzaldehyde. Analysis is due to the absence of benzene rings, and the aldehyde group of octadecyl aldehyde is more likely to react with the group of chitosan to generate a stable amine bond (-NH-C18H37). The presence of benzene rings in octadecyl benzaldehyde may produce a certain steric hindrance effect on the reactivity of the aldehyde group, reducing the efficiency of its reaction with the amino group on chitosan.
[0016] Furthermore, the surfactant includes sodium dodecylbenzene sulfonate, ammonium dodecyl alcohol ether sulfate (CAS No. 67762-19-0), and sodium α-olefin sulfonate (CAS No. 68439-57-6) in a weight ratio of 1: (1.2-1.5): (0.5-0.7).
[0017] Furthermore, the method for modifying the Tencel fiber web is as follows:
[0018] S1: Mix nano zinc oxide, nano titanium oxide, graphene, silane coupling agent KH550 and distilled water in a weight ratio of 1: (0.3-0.5): (1.2-1.4): (0.02-0.05): (500-550), and perform ultrasonic treatment at a frequency of 30-40 KHz for a time of 1.5-2 h to obtain a modified mixed solution;
[0019] S2: soaking the Tencel fiber web in the mixed solution, heating and pressurizing at 90-93° C. and 0.5-0.7 MPa for 10-12 h; washing and drying to obtain a modified Tencel fiber web.
[0020] Furthermore, the volume ratio of the Tencel fiber web to the modified mixed liquid is 1:(2-4).
[0021] The present invention can improve the antibacterial property of the mask cloth and the air permeability of the mask cloth by using a compounded nano material for modification. Through the above treatment, a large number of microporous structures are formed in the Tencel fiber net. These micropores not only increase the surface area of the fiber net, but also provide more channels, allowing air and water vapor to pass more easily, thereby improving the air permeability. The modification treatment can make the Tencel fibers more evenly arranged, reduce the close stacking between the fibers, and increase the space for air circulation. The modified Tencel fiber net has better hydrophilicity and can further increase the liquid absorption.
[0022] Furthermore, the mass ratio of the modified cotton fiber layer to the modified tencel fiber layer is (4-5):(3-4).
[0023] Furthermore, the fineness of the cotton fiber is 3.7-4.2 micronaire and the length is 25-30 mm, and the fineness of the tencel fiber is 1.33 dtex and the length is 35-42 mm.
[0024] Furthermore, the weight of the modified cotton fiber web is 30-50 g / m 2 The weight of modified Tencel fiber web is 40-55g / m 2 .
[0025] Furthermore, the hydroentanglement treatment adopts three hydroentanglement treatments, namely, drum hydroentanglement, flat mesh hydroentanglement, and flat mesh hydroentanglement. The hydroentanglement pressures of the three hydroentanglement treatments are 0.8-0.9MPa, 7-8MPa, and 13-15MPa, respectively.
[0026] The invention provides a highly elastic and breathable cream mask cloth prepared by the preparation method.
[0027] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0028] 1. The present invention provides a highly elastic and breathable cream mask cloth and a preparation method thereof. The mask cloth is blended with natural fibers and synthetic fibers in a specific ratio, and a mask base cloth with high elasticity and good breathability is prepared through special weaving technology and post-processing technology. The membrane cloth can effectively carry cream-like skin care products while ensuring that the skin breathes smoothly and avoids stuffiness. The present invention also provides a preparation method for the membrane cloth, including the steps of fiber selection, blending ratio adjustment, weaving, and post-processing. The membrane cloth is suitable for all skin types, especially for skin that needs deep nourishment and moisturizing, and can significantly improve the moisture content and elasticity of the skin after use.
[0029] 2. The cream mask cloth of the present invention is composed of two layers in total, the first layer is a non-woven fabric layer, and the second layer is an elastic layer. The above two layers are mainly compounded by PUR glue. In order to ensure that the mask cloth has good softness and ductility after compounding, it can have a good application effect; the glue weight of the glue is below 5g / m2, and it needs to be evenly dispersed without affecting the breathability. The glue roller of the present invention needs to have special requirements. The glue application area accounts for 10%-20%, and the glue application part is circular, and the circular diameter is 0.5-1mm and is evenly distributed. The gluing method is the gluing process on the gravure plate. The depth of the gluing concave point of the gravure roller is 0.2-0.8mm, the material is ceramic, and the solid content of the glue is 20%-50%. This can ensure that the glue point position has good softness, and there will be no difference in skin feel between the glue point position and the non-glue point position.
[0030] 3. The present invention can improve the liquid absorption of the facial mask cloth by modifying the cotton fiber, and can absorb more cream essence, which means that more moisturizing ingredients can be absorbed by the skin, thereby providing a longer-lasting moisturizing effect.
[0031] 4. The present invention can improve the antibacterial property of the facial mask cloth and the air permeability of the facial mask cloth by using compound nanomaterials for modification. DETAILED DESCRIPTION
[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] PUR glue was purchased from Shenzhen Meikeyi New Materials Co., Ltd.
[0034] Example 1
[0035] This embodiment provides a method for preparing a highly elastic and breathable cream mask cloth, the preparation method comprising the following steps:
[0036] (1) opening the cotton fibers by a loosening machine, and then feeding them into a cotton box of a carding machine for carding to obtain a cotton fiber web; placing the cotton fiber web in a closed cotton bunker, spraying a modifier into the cotton bunker, wherein the modifier comprises raw materials in parts by weight: 13 parts of modified chitosan, 16 parts of polyethylene glycol, 6 parts of a surfactant, and 115 parts of water; setting the cotton bunker temperature to 47° C. for simmering treatment for 8 hours, subjecting the cotton bunker to a natural cooling treatment, during which a steam valve in the cotton bunker is opened to spray steam humidification to a humidity of 16%; closing the steam valve, setting the cotton bunker temperature to 50° C. for simmering treatment for 32 hours, and after cooling to room temperature, opening the cotton bunker to obtain the modified cotton fiber web;
[0037] The added amount of the modifier is 42% of the mass of the cotton fiber web.
[0038] The preparation method of modified chitosan comprises the following steps: adding 5 parts by weight of chitosan to 170 parts by weight of acetic acid aqueous solution with a volume concentration of 3%, and after dissolving, continuously adding 130 parts by weight of ethanol, adjusting the pH value to 5.5 with 0.15 mol / L sodium hydroxide aqueous solution, adding 0.6 parts by weight of octadecyl aldehyde and 0.005 parts by weight of sodium cyanoborohydride, stirring at 27°C for 28 hours, adjusting the pH value to 7 with 0.15 mol / L sodium hydroxide aqueous solution, adding 230 parts by weight of ethanol for precipitation, centrifuging, washing, and freeze-drying to obtain modified chitosan.
[0039] Chitosan was purchased from Qingdao Bozhi Huili Biotechnology Co., Ltd., water-soluble chitosan, deacetylation degree ≥ 90%. Octadecyl aldehyde: CAS: 638-66-4.
[0040] The surfactant comprises sodium dodecylbenzene sulfonate, ammonium dodecyl alcohol ether sulfate (CAS No. 67762-19-0), and sodium α-olefin sulfonate (CAS No. 68439-57-6) in a weight ratio of 1:1.3:0.6.
[0041] The Tencel fibers are opened by an opener, and then fed into a cotton box of a carding machine for carding to obtain a Tencel fiber web, and the Tencel fiber web is modified to obtain a modified Tencel fiber web;
[0042] The fineness of cotton fiber is 3.9 micronaire and the length is 28 mm; the fineness of Tencel fiber is 1.33 dtex and the length is 40 mm. Tencel fiber was purchased from Jiangsu Jinrongtai New Material Technology Co., Ltd., and cotton fiber was purchased from WenJian Medical Co., Ltd.
[0043] The basis weight of the cotton modified cotton fiber web is 45g / m 2 The weight of modified Tencel fiber web is 42g / m 2 .
[0044] (2) The modified cotton fiber web and the modified Tencel fiber web are laid flat and then subjected to hydroentanglement treatment. The hydroentanglement treatment adopts three hydroentanglement treatments, namely, drum hydroentanglement, flat net hydroentanglement, and flat net hydroentanglement. The hydroentanglement pressures of the three hydroentanglement treatments are 0.9MPa, 8MPa, and 13MPa, respectively; a modified cotton fiber layer and a modified Tencel fiber layer are obtained respectively, and the mass ratio of the modified cotton fiber layer and the modified Tencel fiber layer is 4:3, wherein the thickness of the modified cotton fiber layer is 0.24, and the thickness of the modified Tencel fiber is 0.20mm. The modified cotton fiber layer and the modified Tencel fiber layer are compounded by PUR glue; the glue weight of the PUR glue is 3g / m 2 The glue application area accounts for 15% of the mask cloth, and the glue application area is circular and evenly distributed; the glue application method is the gravure gluing process, the depth of the gravure roller's gluing concave points is 0.5mm, and the material is ceramic; a highly elastic and breathable cream mask cloth is obtained.
[0045] The method for modifying the Tencel fiber web is as follows:
[0046] S1: Mix nano zinc oxide, nano titanium oxide, graphene, silane coupling agent KH550 and distilled water in a weight ratio of 1:0.4:1.3:0.04:500, and perform ultrasonic treatment at a frequency of 35 KHz for 1.7 h to obtain a modified mixed solution;
[0047] The particle size of nano zinc oxide is 30-50nm and the specific surface area is 15-30m2 / g. Zhejiang Zhitai Nano Micro New Materials Co., Ltd. The particle size of nano titanium oxide is 5-15nm, and the specific surface area is 30-50m 2 / g. Purchased from Beijing Dekedaojin Technology Co., Ltd. The D50 value of graphene is 500nm, purchased from Qingdao Xingang Graphite Technology Co., Ltd.
[0048] S2: soaking the Tencel fiber web in the mixed solution, wherein the volume ratio of the Tencel fiber web to the modified mixed solution is 1:3, heating and pressurizing at 92°C and 0.6MPa for 11h; washing with water, and drying to obtain the modified Tencel fiber web.
[0049] Example 2
[0050] This embodiment provides a method for preparing a highly elastic and breathable cream mask cloth, the preparation method comprising the following steps:
[0051] (1) opening the cotton fibers by a loosening machine, and then feeding them into a cotton box of a carding machine for carding to obtain a cotton fiber web; placing the cotton fiber web in a closed cotton bunker, spraying a modifier into the cotton bunker, wherein the modifier comprises the following raw materials in parts by weight: 12 parts of modified chitosan, 18 parts of polyethylene glycol, 4 parts of a surfactant, and 120 parts of water; setting the cotton bunker temperature at 50° C. for a simmering treatment for 9 hours, subjecting the cotton bunker to a natural cooling treatment, during which a steam valve in the cotton bunker is opened to spray steam humidification until the humidity is 17%; closing the steam valve, setting the cotton bunker temperature at 47° C. for a simmering treatment for 30 hours, and after cooling to room temperature, opening the cotton bunker to obtain the modified cotton fiber web;
[0052] The added amount of the modifier is 45% of the mass of the cotton fiber web.
[0053] The preparation method of modified chitosan comprises the following steps: adding 5 parts by weight of chitosan to 160 parts by weight of acetic acid aqueous solution with a volume concentration of 4%, and after dissolving, continuously adding 140 parts by weight of ethanol, adjusting the pH value to 6 with 0.1 mol / L sodium hydroxide aqueous solution, adding 0.8 parts by weight of octadecyl aldehyde and 0.004 parts by weight of sodium cyanoborohydride, stirring at 30°C for 25 hours, adjusting the pH value to 7 with 0.2 mol / L sodium hydroxide aqueous solution, adding 240 parts by weight of ethanol for precipitation, centrifuging, washing, and freeze-drying to obtain modified chitosan.
[0054] Chitosan was purchased from Qingdao Bozhi Huili Biotechnology Co., Ltd., water-soluble chitosan, deacetylation degree ≥ 90%. Octadecyl aldehyde: CAS: 638-66-4.
[0055] The surfactant comprises sodium dodecylbenzene sulfonate, ammonium dodecyl alcohol ether sulfate (CAS No. 67762-19-0), and sodium α-olefin sulfonate (CAS No. 68439-57-6) in a weight ratio of 1:1.5:0.5.
[0056] The Tencel fibers are opened by an opener, and then fed into a cotton box of a carding machine for carding to obtain a Tencel fiber web, and the Tencel fiber web is modified to obtain a modified Tencel fiber web;
[0057] The fineness of cotton fiber is 4.0 micronaire and the length is 30 mm, and the fineness of Tencel fiber is 1.33 dtex and the length is 38 mm.
[0058] The weight of the modified cotton fiber web is 30g / m 2 The weight of modified Tencel fiber web is 40g / m 2 .
[0059] (2) The modified cotton fiber web and the modified Tencel fiber web were laid flat and then subjected to hydroentanglement treatment. The hydroentanglement treatment used three hydroentanglement treatments, namely, drum hydroentanglement, flat net hydroentanglement, and flat net hydroentanglement. The hydroentanglement pressures of the three hydroentanglement treatments were 0.9 MPa, 8 MPa, and 13 MPa, respectively; a modified cotton fiber layer and a modified Tencel fiber layer were obtained, and the mass ratio of the modified cotton fiber layer to the modified Tencel fiber layer was 5:3. The modified cotton fiber layer and the modified Tencel fiber layer were compounded with PUR glue; the glue weight of the PUR glue was 4 g / m 2 The glue application area accounts for 10% of the mask cloth, and the glue application area is circular and evenly distributed; the glue application method is the gravure gluing process, the gravure roller's gluing concave point depth is 0.8mm, and the material is ceramic; a highly elastic and breathable cream mask cloth is obtained.
[0060] The method for modifying the Tencel fiber web is as follows:
[0061] S1: Mix nano zinc oxide, nano titanium oxide, graphene, silane coupling agent KH550 and distilled water in a weight ratio of 1:0.3:1.2:0.02:500, and perform ultrasonic treatment at a frequency of 30 KHz for 2 h to obtain a modified mixed solution;
[0062] The particle size of nano zinc oxide is 30-50nm and the specific surface area is 15-30m 2 / g. Zhejiang Zhitai Nano Micro New Materials Co., Ltd. The particle size of nano titanium oxide is 5-15nm, and the specific surface area is 30-50m 2 / g. Purchased from Beijing Dekedaojin Technology Co., Ltd. The D50 value of graphene is 500nm, purchased from Qingdao Xingang Graphite Technology Co., Ltd.
[0063] S2: soaking the Tencel fiber web in the mixed solution, wherein the volume ratio of the Tencel fiber web to the modified mixed solution is 1:4, heating and pressurizing at 90°C and 0.7MPa for 12h; washing with water, and drying to obtain the modified Tencel fiber web.
[0064] Comparative Example 1
[0065] The difference between this comparative example and Example 1 is that the modified chitosan is replaced by chitosan. Chitosan is purchased from Qingdao Bozhi Huili Biotechnology Co., Ltd., water-soluble chitosan, and the degree of deacetylation is ≥90%. Octadecyl aldehyde: CAS: 638-66-4.
[0066] Comparative Example 2
[0067] The difference between this comparative example and Example 1 is that octadecyl aldehyde is replaced by octadecyl benzaldehyde (CAS No.: 20895-38-7).
[0068] Comparative Example 3
[0069] The difference between this comparative example and Example 1 is that the surfactant includes sodium dodecylbenzene sulfonate, ammonium dodecyl alcohol ether sulfate (CAS No. 67762-19-0), and sodium α-olefin sulfonate (CAS No. 68439-57-6) in a weight ratio of 1:1:1.
[0070] Comparative Example 4
[0071] The difference between this comparative example and Example 1 is that the Tencel fiber web is not modified.
[0072] Comparative Example 5
[0073] The difference between this comparative example and Example 1 is that nano zinc oxide, nano titanium oxide, graphene, silane coupling agent KH550 and distilled water are mixed in a weight ratio of 0.4:1.3:1:0.04:500.
[0074] Comparative Example 6
[0075] The difference between this comparative example and Example 1 is that the particle size of nano zinc oxide is 70-90nm, and the specific surface area is 5-10m 2 / g. Zhejiang Zhitai Nano Micro New Materials Co., Ltd. The particle size of nano titanium oxide is 40-50nm, and the specific surface area is 10-20m 2 / g. Purchased from Beijing Dekedaojin Technology Co., Ltd. The D50 value of graphene is 1000nm, purchased from Qingdao Xingang Graphite Technology Co., Ltd.
[0076] Performance Testing
[0077] The highly elastic and breathable cream mask fabrics prepared in Examples 1-2 and Comparative Examples 1-6 were used as samples for performance testing.
[0078] (1) Elasticity test: The tensile strength and elongation at break of the samples were tested in accordance with GB / T24218.3-2010. Five samples were taken along the machine output direction (longitudinal direction) and the cloth width direction (transverse direction). The samples were at least 100 mm away from the edge of the cloth, with a width of 50 mm and a length that met the clamping distance of 200 mm. After the test, the average tensile strength and elongation at break of the five longitudinal samples were calculated.
[0079] (2) Air permeability test: The air permeability of the sample was tested in accordance with GB / T24218.15-2018. The sample was cut from 5 randomly selected areas. The sample size was 100*100mm. The pressure difference of the airflow of the vacuum pump on the upper and lower surfaces of the sample was 200Pa. The circular test area of the test head was 20cm 2 , take the average value after the test is completed.
[0080] (3) Liquid absorption test: According to GB / T24218.6-2010 "Liquid absorption of test samples", 5 samples are cut from 5 randomly selected areas, and the sample size is 100*100mm. The average value is taken after the test is completed.
[0081] (4) Antibacterial rate test: Oscillation method, to detect its antibacterial rate against Staphylococcus aureus.
[0082] The results are shown in Table 1.
[0083] Table 1 Performance test results
[0084]
[0085] The physical property requirements of spunlace nonwoven fabrics for facial mask membranes are shown in Table 2.
[0086] Table 2 Physical performance requirements of spunlace nonwoven fabrics for facial mask fabrics
[0087]
[0088] For facial mask cloth, the higher the longitudinal breaking strength and the smaller the longitudinal breaking elongation, the easier it is to put on the machine; if the longitudinal elongation is too high, it will be pulled too much when put on the machine, which will easily cause the product to deform, causing the expected facial mask size to deviate and fail to achieve the desired effect. Usually, during the production process, the tension of the membrane cloth is controlled at 20N-40N. If the tension is too small, wrinkles are likely to appear during the production process, resulting in the product being not flat enough; if the tension is too large, the membrane cloth is easily deformed and even torn.
[0089] It can be seen from the above performance test results that the comprehensive performance of the cream mask fabric of Examples 1-2 is excellent. However, the comparative examples are significantly worse than the embodiments in terms of corresponding performance tests because they do not adopt the necessary technical solutions. In Comparative Example 1, chitosan is not modified, and the liquid absorption decreases. In Comparative Example 2, octadecyl aldehyde is replaced with octadecyl benzaldehyde, and the liquid absorption decreases. In Comparative Example 3, the surfactant is different, and the liquid absorption decreases. In Comparative Example 4, the Tencel fiber mesh is not modified, and the antibacterial and air permeability decrease. In Comparative Example 5, the nano zinc oxide, nano titanium oxide, and graphene have different ratios, and the antibacterial and air permeability decrease. In Comparative Example 6, the parameters of nano zinc oxide, nano titanium oxide, and graphene are different, and the antibacterial and air permeability decrease. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.
[0090] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a highly elastic and breathable cream mask fabric, characterized in that: The preparation method comprises the following steps: (1) opening the cotton fibers by a loosening machine, and then feeding them into a cotton box of a carding machine for carding to obtain a cotton fiber web; placing the cotton fiber web in a closed cotton bunker, spraying a modifier into the cotton bunker, wherein the modifier comprises the following raw materials in parts by weight: 12-15 parts of modified chitosan, 15-18 parts of polyethylene glycol, 4-7 parts of a surfactant, and 110-120 parts of water; setting the cotton bunker temperature to 45-50° C. for simmering treatment for 7-9 hours, subjecting the cotton bunker to a natural cooling treatment, during which a steam valve in the cotton bunker is opened to spray steam humidification until the humidity is 15-17%; closing the steam valve, setting the cotton bunker temperature to 47-52° C. for simmering treatment for 30-35 hours, and after cooling to room temperature, opening the cotton bunker to obtain the modified cotton fiber web; The Tencel fibers are opened by an opener, and then fed into a cotton box of a carding machine for carding to obtain a Tencel fiber web, and the Tencel fiber web is modified to obtain a modified Tencel fiber web; (2) The modified cotton fiber web and the modified Tencel fiber web are laid flat, and then subjected to hydroentanglement treatment to obtain a modified cotton fiber layer and a modified Tencel fiber layer, respectively. The modified cotton fiber layer and the modified Tencel fiber layer are compounded with PUR glue; the glue weight of the PUR glue is 3-4 g / m 2 The glue application area accounts for 10%-20% of the mask cloth, and the glue application area is circular and evenly distributed; the glue application method is a concave plate gluing process, the depth of the gluing concave points of the concave plate roller is 0.2-0.8mm, and the material is ceramic; a highly elastic and breathable cream mask cloth is obtained.
2. The method for preparing the highly elastic and breathable cream mask cloth according to claim 1, characterized in that: The added amount of the modifier is 40-45% of the mass of the cotton fiber web.
3. The method for preparing the highly elastic and breathable cream mask cloth according to claim 1, characterized in that: The preparation method of modified chitosan comprises the following steps: adding 5 parts by weight of chitosan to 160-180 parts by weight of acetic acid aqueous solution with a volume concentration of 2-4%, and after dissolving, continuously adding 120-140 parts by weight of ethanol, adjusting the pH value to 5-6 with 0.1-0.2 mol / L sodium hydroxide aqueous solution, adding 0.4-0.8 parts by weight of octadecyl aldehyde and 0.004-0.006 parts by weight of sodium cyanoborohydride, stirring at 25-30 DEG C for 25-30 hours, adjusting the pH value to 7 with 0.1-0.2 mol / L sodium hydroxide aqueous solution, adding 220-240 parts by weight of ethanol for precipitation, centrifuging, washing, and freeze-drying to obtain modified chitosan.
4. The method for preparing the highly elastic and breathable cream mask cloth according to claim 1, characterized in that: The surfactant comprises sodium dodecylbenzene sulfonate, ammonium dodecyl alcohol ether sulfate and sodium alpha-olefin sulfonate in a weight ratio of 1: (1.2-1.5): (0.5-0.7).
5. The method for preparing the highly elastic and breathable cream mask cloth according to claim 1, characterized in that: The method for modifying the Tencel fiber web is as follows: S1: Mix nano zinc oxide, nano titanium oxide, graphene, silane coupling agent KH550 and distilled water in a weight ratio of 1: (0.3-0.5): (1.2-1.4): (0.02-0.05): (500-550), and perform ultrasonic treatment at a frequency of 30-40 KHz for a time of 1.5-2 h to obtain a modified mixed solution; S2: soaking the Tencel fiber web in the mixed solution, heating and pressurizing at 90-93° C. and 0.5-0.7 MPa for 10-12 h; washing and drying to obtain a modified Tencel fiber web.
6. The method for preparing the highly elastic and breathable cream mask cloth according to claim 1, characterized in that: The volume ratio of the Tencel fiber web to the modified mixed liquid is 1:(2-4).
7. The method for preparing the highly elastic and breathable cream mask cloth according to claim 1, characterized in that: The mass ratio of the modified cotton fiber layer to the modified tencel fiber layer is (4-5):(3-4).
8. The method for preparing the highly elastic and breathable cream mask cloth according to claim 1, characterized in that: The fineness of cotton fiber is 3.7-4.2 micronaire and the length is 25-30mm, and the fineness of Tencel fiber is 1.33dtex and the length is 35-42mm.
9. The method for preparing the highly elastic and breathable cream mask cloth according to claim 1, characterized in that: The weight of the modified cotton fiber web is 30-50g / m 2 The weight of modified Tencel fiber web is 40-55g / m 2 .
10. A highly elastic and breathable cream mask cloth prepared according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Cotton fiber repairing agent and cotton fiber repairing method thereof
CN108867052A
Zinc oxide powder for antibacterial tencel and preparation method thereof
CN110592694A
Alkyl chitosan-graphene oxide composite sponge and preparation method and application thereof
US20200316248A1
Unidirectional water-guiding facial mask base material and preparation method therefor
WO2022062830A1